HUBUNGAN ANTARA DUKUNGAN KELUARGA, SIKAP DAN MOTIVASI IBU TERHADAP KETEPATAN PEMBERIAN MP-ASI PADA BAYI USIA 6-23 BULAN DI PUSKESMAS CISAUK TAHUN 2022 - Shinta Mona Lisca; Riezka Putri Nabila (Jurnal Kebidanan, 2022)
Early breastfeeding is one of the causes of the high infant mortality rate in Indonesia. The Cisauk District Health Center in 2021 achieved the target of exclusive breastfeeding in accordance with the target of the Tangerang District Health Office, which was 60%. This study aims to determine the relationship between family support, attitudes and mother's motivation to the accuracy of complementary feeding for breastfeeding aged 6-23 months at the Puskesmas Cisauk District, Tangerang Regency in 2022. The research design used a cross sectional. The sample is 80 respondents using probability sampling technique. The research instrument used a questionnaire. Data analysis used univariate and bivariate. The results showed that 27.5% of respondents did not provide complementary feeding, 39% of respondents did not receive family support, 35% of respondents had a negative attitude, 28% of respondents were not motivated. There is a significant relationship between family support (p =0,037), attitude (p =0,001) and motivation (p = 0.004) on the accuracy of giving complementary feeding aged 6-23 months at the Cisauk Public Health Center, Tangerang Regency in 2022. The accuracy of giving complementary feeding influenced by family support, mother's attitude and motivation, It is hoped that mothers will pay more attention to when the right time is in giving complementary feeding, starting from the age of 6-23 months, mothers can be motivated in giving complementary feeding such as seeking more information from health workers , the internet as well as family and closest people, get maximum support from every family member as well as a positive mother's attitude about giving the right and proper complementary feeding. It is hoped that mothers can increase motivation related to accuracy in giving MP-ASI for infants aged 6-23 months by increasing knowledge and understanding about the importance of giving MP-ASI.